Dialogues with parents: a parental support and empowerment program based on the Touchpoints Model - Brito, Ana Teresa; Xavier, Maria Raul; Azevedo, Nair; Fareleira, Filipa; Espirito Santo, Joana; Teixeira, Lina; Tinoco, Joana; Singer, Jayne (Frontiers in Education, 2023)
"Dialogues with Parents-welcoming, listening, empowering" aimed to understand the impact of an innovative approach supporting parents with identified social/emotional vulnerabilities. Program goals included promotion of positive parenting, expansion of parents’ knowledge and skills, and enhancement of parent-child interactions. Based on the Brazelton Touchpoints Developmental-Relational Frameworks, the program applied strengths-based assumptions and relationship-based practices to underpin empathic and collaborative relationships with families, seeking to strength their confidence in parenting. Two modalities were offered with a modular structure from Prenatal-Newborn to 6 years. Both included 10 modules, one in which the same group of parents carried out the complete sequence of sessions (Continuous Group), and a second in which parents selected one Touchpoint according to their needs and “drop in” to the session(s) of their choice (Touchpoints 1 by 1 Group). Data was gathered through satisfaction questionnaires at the end of each encounter. A focus group was also held with parents from the Continuous Group. The difference between applications (248) and total participation (99) indicates that parent’s interest in participating is high but only a third managed to join the groups. Nevertheless, results were very positive, highlighting the quality of the Touchpoints approach and program implementation, namely its impact on improving parents’ understanding of children’s development and of their own role in parenting. Parents particularly valued the opportunity to actively participate in the encounters and, in the Continuous Group, the usefulness of the encounters for themselves as a person and as parents.